Copy Number Variation of FCGR3B on Negrito-Mendriq / Mohd Helmy Yusof, Umi Shakina Haridan and Muhamad Rahimi Che Hassan - Yusof, Mohd Helmy; Haridan, Umi Shakina; Che Hassan, Muhamad Rahimi (Universiti Teknologi MARA, Negeri Sembilan, 2019)
Fc Gamma Receptor 3B (FcγRIIIB, encoded by the gene FCGR3B) plays a crucial role in immunity response activated by cellular effectors and regulatory functions. Copy number variation (CNV) of this gene has been previously reported to affect susceptibility to several diseases such as autoimmune diseases and chronic inflammatory response. One of the rarest and smallest tribes of Orang Asli which is Negrito-Mendriq sample was used as a subject in this study. Twenty-two (22) Lymphoblastoid cell lines (LCLs) of Negrito-Mendriq was obtained from the deposited cell archive, Institute Medical Molecular Biotechnology, IMMB (UiTM Sg Buloh, Selangor, Malaysia) and the LCLs were revived. The DNA was extracted from the LCL and finally PRT - REDVR assay was carried for FCGR3B copy number genotyping. Analysis revealed that copy number 2 demonstrated the highest distribution for FCGR3B (90.9%); whilst no copy number loss was found for FCGR3B. For high copy number (>2), 9.1% was obtained. Copy number greater than 3 (>3) was not found in this study. Finally, it was concluded that no significant difference of CNV of FCGR3B for Orang Asli Negrito-Mendriq when compared with the reported studies. CNV of FCGR3B genes of Negrito-Mendriq was found normal in this study, where the pattern of copy number distribution was almost similar with previously reported studies.